Mujeres, representaciones y objetos de la cultura material en la Audiencia de Quito en el último cuarto del siglo XVIII (Estudios) - Borrero Vega, Ana Luz (2023)
The configuration of the female subject in the Audiencia of Quito at the end of the 18th century is examined with a focus on the objects associated with elite-class women in Cuenca—pictures, portraits, paintings, and other pieces consigned in dowries and wills. The article is especially concerned with clothing, jewelry, ornaments, and other items that enable establishing social differentiations and show economic aspects and ethnicity. The study contributes to an analysis of material culture during the late colonial period in the southern region of Ecuador.